Effectiveness of vaccine against pandemic influenza A/H1N1 among people with underlying chronic diseases: cohort study, Denmark, 2009-10. (25th January 2012) - Emborg, Hanne-Dorthe; Krause, Tyra Grove; Hviid, Anders; Simonsen, Jacob; Mølbak, Kåre
Abstract : Objective To determine the effectiveness of an adjuvanted monovalent vaccine against pandemic influenza A/H1N1 among people with underlying chronic diseases. Design Historical cohort study. Setting Mandatory national reporting systems, 2 November 2009 to 31 January 2010, Denmark. Participants 388 069 people under 65 years of age with a diagnosis in the past five years of at least one underlying disease expected to increase the risk of severe illness after influenza. Main outcome measures Laboratory confirmed H1N1 infection and influenza related hospital admission with laboratory confirmed H1N1 infection. Estimates of vaccine effectiveness were adjusted for age and underlying disease. Results The effectiveness of pandemic vaccine against confirmed H1N1 infection 14 days after one dose of vaccine was 49% (95% confidence interval 10% to 71%). The effectiveness of vaccine against admission to hospital for confirmed H1N1 infection was 44% (−19% to 73%). Conclusions The adjuvanted monovalent vaccine against pandemic influenza A/H1N1 was offered late in the 2009-10 influenza season. Among chronically ill people, this vaccine offered protection against laboratory confirmed H1N1 infection but only offered non-significant protection against influenza related hospital admissions confirmed as H1N1 infection. This finding is of public health relevance because the population of chronically ill people is a major target group for pandemic vaccinations and because of the delayed availability of pandemic vaccines in a forthcoming pandemic.